Awareness on the Mental Health Law of Registered Social Workers in Negros Occidental - Patricio, Adrian L.; Verdeprado, Richelle H. (Philippine Social Science Journal, 2020)
Mental health is the condition of an individual’s well-being. Mentally healthy individuals realize their abilities, cope effectively with the everyday stresses encountered in life, show resilience during extreme events in life, perform efficiently, and participate in the community’s development. The global concern of mental health issues is enormous, under-appreciated, and mostly not fulfilled. Hence, the paper assessed the awareness on the Mental Health Law of the registered social workers in Negros Occidental in the areas of general provisions, psychiatric, neurologic, and psychosocial services. It also social workers’ mental health services in educational institutions, communities, hospitals, government agencies, and non-governmental organizations.